A Malagasy element in Continental Africa: a new subspecies of the rare Amauris nossima (Nymphalidae, Danainae) from the Kenyan coast. Issue 4 (1st October 2020) - Pyrcz, Tomasz W; Collins, Steve; Lachowska-Cierlik, Dorota; Lees, David C; Sáfian, Szabolcs; Florczyk, Klaudia
Abstract : Amauris nossima Ward (Nymphalidae, Danainae) was known before this study only from Madagascar and the island of Mayotte, without clearly defined subspecies, but with five names considered invalid or infrasubspecific. It has generally been considered a rare species of butterfly classified by IUCN as vulnerable (Vu B1 + 2c). Here, it is reported for the first time from continental Africa. A new subspecies A. nossima mrima n. ssp. is described from two remnants of rain forest, Mrima and Buda, on the southern Kenyan coast, where it occurs sympatrically with Amauris ochlea Boisduval, widely distributed in East Africa. Their, previously predicted, sister-species status is confirmed by morphological (male and female genitalia) and partial mitochondrial (COI) data. The finding of A. nossima in Kenya opens the discussion on a possible recolonization of Africa from Madagascar, which would be an exception to a predominant biogeographical pattern of African origin of Malagasy butterflies via overseas dispersal.